2011
DOI: 10.1029/2010jb007944
|View full text |Cite
|
Sign up to set email alerts
|

Elevated gas hydrate saturation within silt and silty clay sediments in the Shenhu area, South China Sea

Abstract: [1] Gas hydrate saturations were estimated using five different methods in silt and silty clay foraminiferous sediments from drill hole SH2 in the South China Sea. Gas hydrate saturations derived from observed pore water chloride values in core samples range from 10 to 45% of the pore space at 190-221 m below seafloor (mbsf). Gas hydrate saturations estimated from resistivity (R t ) using wireline logging results are similar and range from 10 to 40.5% in the pore space. Gas hydrate saturations were also estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 84 publications
(122 reference statements)
2
85
0
Order By: Relevance
“…During the recent years, in the northern continental margin of the South China Sea, scientists found abundant gas hydrate accumulations, especially in the Shenhu area (close to the current study area) (Zhang et al, 2002;Wang et al, 2011;Wu et al, 2007;Lin et al, 2009). Sun et al (2012) identified two types of tectonically and stratigraphically controlled fluid flow related systems in the deep-water area of the Baiyun Sag adjacent to our current study area.…”
Section: The Relationship Among the Focused Fluid The Slope Failure mentioning
confidence: 66%
“…During the recent years, in the northern continental margin of the South China Sea, scientists found abundant gas hydrate accumulations, especially in the Shenhu area (close to the current study area) (Zhang et al, 2002;Wang et al, 2011;Wu et al, 2007;Lin et al, 2009). Sun et al (2012) identified two types of tectonically and stratigraphically controlled fluid flow related systems in the deep-water area of the Baiyun Sag adjacent to our current study area.…”
Section: The Relationship Among the Focused Fluid The Slope Failure mentioning
confidence: 66%
“…Such a character contrasts with areas of the South China Sea (e.g. Wang et al, 2011;Wang et al, 2014), including around the Dongsha Uplift, in which gas hydrates were systematically observed in near-seafloor sediment Wu et al, 2005).…”
Section: Evidence Of Associated Slope Failure and Channel Incision Inmentioning
confidence: 70%
“…Acoustic impedance computed from seismic data can be used to estimate gas hydrate saturations (Lu and McMechan 2002;Dai et al 2008;Wang et al 2011;Riedel and Shankar 2012) using various post-stack impedance inversion methods of seismic data. In this paper the model-based inversion of Russell and Hampson (1991) was used as implemented in the Hampson Russell STRATA software package.…”
Section: Methodsmentioning
confidence: 99%